2012
DOI: 10.9773/sosei.53.569
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Stretch Flange Ability of High-Tensile-Strength Steel Sheets by Piercing under Tension Using Humped Bottom Punch

Abstract: To meet the requirements for the weight reduction of automobiles, high-tensile-strength steel sheets have been applied extensively to the manufacture of auto parts. But their relatively lower press formability has obstructed their further application, and it is strongly demanded that the stretch flange ability of such steel sheets be increased, and cracks that occur when stretching edges during the press forming of such steel sheets be suppressed. Thus the authors have carried out a study to improve the stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Edge formability is another mechanical characteristic that is important for automotive components. Several studies have demonstrated a correlation between this aspect and the material fracture toughness [35][36][37][38][39][40][41]. Takahashi et al [35] found that the edge flangeability of hot rolled high strength steels is linearly correlated with their fracture toughness Edge formability is another mechanical characteristic that is important for automotive components.…”
Section: Mechanical Properties and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Edge formability is another mechanical characteristic that is important for automotive components. Several studies have demonstrated a correlation between this aspect and the material fracture toughness [35][36][37][38][39][40][41]. Takahashi et al [35] found that the edge flangeability of hot rolled high strength steels is linearly correlated with their fracture toughness Edge formability is another mechanical characteristic that is important for automotive components.…”
Section: Mechanical Properties and Applicationsmentioning
confidence: 99%
“…Several studies have demonstrated a correlation between this aspect and the material fracture toughness [35][36][37][38][39][40][41]. Takahashi et al [35] found that the edge flangeability of hot rolled high strength steels is linearly correlated with their fracture toughness Edge formability is another mechanical characteristic that is important for automotive components. Several studies have demonstrated a correlation between this aspect and the material fracture toughness [35][36][37][38][39][40][41].…”
Section: Mechanical Properties and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4) Methods for reducing springback by changing product shapes and forming methods have also been developed. 5) To resolve forming failures such as cracks and wrinkles, new methods have been developed, such as a shearing technique to increase the elongation limit of the sheet edge and thus counter the cracking at the ends of the steel material (edge cracking), 6,7) and forming methods for avoiding strain concentrations. 8) However, few countermeasures are effective against cracking and wrinkling when forming a complex shape, where the cross-sectional line changes significantly from the forming.…”
Section: Introductionmentioning
confidence: 99%